Circle of Culture and permanent education for transformation of professional practice: an integrative review - Rozal, Juliana Ferreira; Monteiro, Estela Maria Leite Meirelles; Marinus, Maria Wanderleya de Lavor Coriolano; Santos, Tamyris Arcoverde (Ciência & saude coletiva, 2023)
Abstract This article aimed to know the scientific evidence that underlies Culture Circle application as a device of Permanent Education in Health for professional practice transformation. This is an integrative literature review carried out in the PubMed, CINAHL, LILACS and Scopus databases, in October 2021, with the descriptors “health professionals”, “professional practice”, “continuing education”, “health promotion” and the uncontrolled term “Culture Circle”. Data were analyzed in a descriptive way. The results identified 217 articles and five were included to compose the final sample. It was identified that the most discussed themes in Culture Circles were health education and health promotion. There was an average of 13 participants, lasting between one and a half to four hours, with the presence of an animator/researcher and carried out in the workplace. It is concluded that applying Culture Circles in Permanent Education in Health is a powerful inducer of change in professional practice. Recommendations are presented for its application in empowering subjects and in strengthening health promotion actions as well as the need for field research to broaden the understanding of the implication of the method and its consequences in professional practice. Resumo O objetivo é conhecer as evidências científicas que fundamentam a aplicação do Círculo de Cultura como dispositivo de Educação Permanente em Saúde para a transformação da prática profissional. Trata-se de uma revisão integrativa realizada nas bases de dados PubMed, CINAHL, LILACS e Scopus, em outubro de 2021, com os descritores: “profissionais de saúde”, “prática profissional”, “educação permanente”, “promoção à saúde” e do termo não controlado “Círculo de Cultura”. Analisaram-se os dados de modo descritivo. Foram identificados 217 artigos e cinco foram incluídos para compor a amostra final. Identificou-se que as temáticas mais abordadas nos Círculos de Cultura foram Educação em Saúde e Promoção à Saúde, houve uma média de 13 participantes, com duração entre uma hora e meia a quatro horas, com presença do animador/pesquisador e realizados no local de trabalho. Conclui-se que a aplicabilidade do Círculo de Cultura na Educação Permanente em Saúde é um potente indutor de mudança na prática profissional. Apresenta-se recomendações para sua aplicação no empoderamento dos sujeitos e no fortalecimento das ações de promoção à saúde, bem como, a necessidade de pesquisas de campo para ampliar a compreensão da implicação do método e seus desdobramentos na prática profissional.